Comparison of usefulness of clinical diagnostic criteria for hepatocellular carcinoma in a hepatitis B endemic area - So Young Bae; Moon Seok Choi; Geum-Youn Gwak; Yong Han Paik; Joon Hyoek Lee; Kwang Cheol Koh; Seung Woon Paik; Byung Chul Yoo (Clinical and Molecular Hepatology, 2012)
Background/AimsWe compared the accuracy and usefulness of clinical diagnostic criteria for hepatocellular carcinoma in a hepatitis B virus (HBV)-endemic area.MethodsWe reviewed the medical records of 355 patients who had undergone liver resection or biopsy at our institution between January 2008 and December 2009. These patients were reevaluated using four noninvasive diagnostic criteria for hepatocellular carcinoma proposed by the European Association for the Study of the Liver (EASL), the American Association for the Study of Liver Diseases (AASLD), the Korean Liver Cancer Study Group and the National Cancer Center (KLCSG/NCC), and National Comprehensive Cancer Network (NCCN) guidelines.ResultsThe overall sensitivity was highest using the KLCSG/NCC criteria (79.8%), followed by the AASLD (51.5%), EASL (38.4%), and NCCN (10.1%; P<0.001) criteria, whereas the specificity (84.5-98.3%) and positive predictive value (96.2-98.3%) were similar for all of the criteria. The KLCSG/NCC criteria had an acceptable false-positive rate and the highest sensitivity among all of the patients, including those positive for HBsAg, those without liver cancer, and those with a tumor of at least 2 cm.ConclusionsThe KLCSG/NCC and AASLD criteria exhibited the highest sensitivity, and all four guidelines had a high specificity among all of the patients. Based on the sensitivity and false-positive rate, the KLCSG/NCC criteria was the most useful in the majority of patients. Inclusion of HBV infection in the clinical diagnostic criteria for hepatocellular carcinoma would be reasonable and may lead to an improvement in the sensitivity, with acceptable false-positive rates, in HBV-endemic areas.